Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1161/01.res.0000060485.20318.96
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the Cysteine Protease Cathepsin S Impairs Microvessel Growth

Abstract: During angiogenesis, microvascular endothelial cells (ECs) secrete proteinases that permit penetration of the vascular basement membrane as well as the interstitial extracellular matrix. This study tested the hypothesis that cathepsin S (Cat S) contributes to angiogenesis. Treatment of cultured ECs with inflammatory cytokines or angiogenic factors stimulated the expression of Cat S, whereas inhibition of Cat S activity reduced microtubule formation by impairing cell invasion. ECs from Cat S-deficient mice show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
154
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 27 publications
12
154
1
2
Order By: Relevance
“…Moreover, pharmacological inhibition and siRNA interference of CathK impaired EC migration/invasion, proliferation and tubule formation. Among Cat family members, CatS and CatL were shown to contribute to angiogenesis 4,12 . However, the pharmacological inhibition of these Cats did not affect the migration or proliferation of mature ECs or vascular smooth muscle cells 12,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pharmacological inhibition and siRNA interference of CathK impaired EC migration/invasion, proliferation and tubule formation. Among Cat family members, CatS and CatL were shown to contribute to angiogenesis 4,12 . However, the pharmacological inhibition of these Cats did not affect the migration or proliferation of mature ECs or vascular smooth muscle cells 12,15 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that matrix metalloproteinases (MMPs) and serine proteases have essential roles in these processes 2,3 . However, recent evidence shows that other proteolytic pathways, such as the cysteine protease cathepsin (Cat) family, are also involved in angiogenesis 4,5 .…”
mentioning
confidence: 99%
“…3 Although the mechanisms controlling cathepsin activities in smooth muscle cells 11 and macrophages 22,39,40 have been reported, the role of cathepsins in endothelial cells have been rather limited. Shi et al showed that cathepsin S deficiency led to abnormal angiogenic responses attributable to abnormal extracellular matrix degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al showed that cathepsin S deficiency led to abnormal angiogenic responses attributable to abnormal extracellular matrix degradation. 40 Also, cathepsin L has been shown to play an important role in endothelial progenitor cell-mediated neovascularization. 38 Although shear stress has been shown to increase cathepsin B activity in neutrophils, 41 the current study is the first report showing that cathepsins are regulated by shear stress in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal angiogenesis in micro-vascular endothelial cells and defective micro-vessel development during wound repair occurred in Cat S deficient mice. These indicated that Cat S plays an important role in aspects of angiogenesis both in vitro and in vivo 3 . Furthermore, high Cat S expression has also been observed in a range of tumors such as prostate, astrocytomas, hepatocellular and pancreatic carcinomas [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 93%